Village Funds Utilization Strategy to Improve Food Security - Yuliana, Intan (Universitas Negeri Semarang, 2018)
The aim of this study was to analyze food security improvement strategy in line with the potency and problems, so that the utilization of village funds is more optimal and on target in order to support the financing of food security in Kuwu village, Dempet Sub-district, Demak Regency. The type of this research is quantitative research by using SWOT analysis. This research used primary and secondary data. The results of analysis showed that the utilization of Kuwu Village Fund was more concerned with physical development as well as transportation facilities and infrastructure. The results of SWOT analysis showed that the appropriate strategy to improve food security through the use of Village Funds in Kuwu Village is to support aggressive growth policy by maximizing the strengths and opportunities such as increasing food production capacity by intensification and diversification, human resource development, and improving the road infrastructure of farmer business. Tujuan dari penelitian ini adalah untuk menganalisis strategi peningkatan ketahanan pangan sejalan dengan potensi dan permasalahannya, sehingga pemanfaatan dana desa lebih optimal dan tepat sasaran dalam rangka mendukung pembiayaan ketahanan pangan di desa Kuwu, Kecamatan Dempet. , Kabupaten Demak. Jenis penelitian ini adalah penelitian kuantitatif dengan menggunakan analisis SWOT. Penelitian ini menggunakan data primer dan sekunder. Hasil analisis menunjukkan bahwa pemanfaatan Dana Desa Kuwu lebih berkaitan dengan pembangunan fisik serta sarana dan prasarana transportasi. Hasil analisis SWOT menunjukkan bahwa strategi yang tepat untuk meningkatkan ketahanan pangan melalui penggunaan Dana Desa di Desa Kuwu adalah untuk mendukung kebijakan pertumbuhan agresif dengan memaksimalkan kekuatan dan peluang seperti meningkatkan kapasitas produksi pangan dengan intensifikasi dan diversifikasi, pengembangan sumber daya manusia, dan meningkatkan infrastruktur jalan bisnis petani.